The Influence of Supervision, Work Environment, and Job Satisfaction on the Performance of Equipment Employees at the Water Resources, Highways, and Construction Services of Medan City - Putri Kurnia Ridwan; Yohny Anwar; Muhammad Toyib Daulay (Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the influence of supervision, work environment, and job satisfaction on the performance of ASN employees in the Equipment Division of the Department of Water Resources, Highways, and Construction of Medan City. The research employed an associative-quantitative approach with a population consisting of all ASN employees and a sample of 96 respondents selected through a saturated sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression, t-test, F-test, and determination test. The results showed that supervision, work environment, and job satisfaction had a positive and significant effect on employee performance both partially and simultaneously, with a contribution of 77.3% and a relationship strength of 0.879 (very strong). Supervision was the most influential variable compared to the others. These findings confirmed that improving the quality of supervision, non-physical work environment conditions, and job satisfaction played an important role in enhancing the performance of ASN employees.